Translation from Spanish into English of the “Código de la Niñez y Adolescencia” and “ Código de Convivencia” - Jaramillo Tandazo, Yesenia Peregrina (2011)
The present thesis titled: TRANSLATION FROM SPANISH INTO ENGLISH OF THE “CÓDIGO DE LA NIÑEZ Y ADOLESCENCIA” AND “CÓDIGO DE CONVIVENCIA”. It has been made with the purpose of giving an useful contribution for all the people that want to know a little more of the norms and laws of the Childhood and adolescence that govern in our country and that should be complied and respected by all Ecuadorian citizens. This code is in validity from July 3rd, 2003. It contains 4 books, 389 articles and 15 transitory dispositions. It was elaborated to declare the rights that aid all people until 18 years old. The childhood and adolescence code guarantees that the children and adolescents are entitled to: the life from their conception, identity, name and citizenship, health and integral education, social security, to have a family, to enjoy the familiar coexistence and to be consulted in the matters necessary for the community. The Coexistence Code is a ministerial agreement, proposed by the Ministry of education and Culture, and put into practice for the public and private educational institutions of all the levels and modalities of the educational system of the Ecuador. In the Coexistence code are established the rights and responsibilities that students, teachers and authorities of the educational establishments have and the family parents or legal representatives for the fortification and integral development in the exercise of the obligations and rights, to improve the coexistence inside and outside of the educational and that exists and education of quality and warmth. For that reason the present translation has as main objective to show the regulations of integral protection that allow that children and adolescents be treated in an integral way, avoiding that they are only taken into account in certain environments and forgotten in other.